School Based Management: A Strategy to Improve the Quality of Education - Hasnadi; Sudibyo, Hanung; Zikriati (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
Schools have their own challenges and problems that have an impact on differences in the quality of educational goals achieved. This article aims to analyze and describe School-Based Management (SBM) as a school quality improvement concept. This article uses a literature review approach. The SBM concept offers schools autonomy to provide flexibility to schools in the context of equal distribution of education, manage all school resources, make and determine school policies, create independence, increase community participation, develop schools according to the demands and needs of the local community. so that educational goals can be achieved. School responsibilities in implementing SBM as a school quality improvement concept include; teaching and learning process, planning and evaluation of school programs, curriculum management, education and education personnel, school facilities and infrastructure, financing, student services, school relations with the community, and school climate. The principles of SBM implementation are the principles of openness, independence, fairness, partnership, accountability, participatory, democratic, efficiency and quality-oriented. Therefore, education managers must be able to make SBM as a concept to improve the quality of education based on the circumstances, needs and demands of the school environment.